2021
DOI: 10.25259/sni_896_2021
|View full text |Cite
|
Sign up to set email alerts
|

Exoscopic carotid endarterectomy using movable 4K 3D monitor: Technical note

Abstract: Background: Carotid endarterectomy (CEA) using conventional surgical microscope has been already established as golden standard. Recently, exoscope was introduced into the field of neurosurgery, and various merits of it have been reported. We report the experiences of exoscopic CEA using a movable 4K 3D monitor and discuss the feasibility of it. Methods: We report a consecutive series of 15 cases of exoscopic CEA for internal carotid artery (ICA) stenosis using a movable 4K 3D monitor between January 2020 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…[ 11 ] However, when using ORBEYE for the midline suboccipital approach, the operator can perform stable manipulations in a comfortable posture from the rostral end of the patient with slight head-down position, regardless of the operative site and visual axis. In addition, as we previously indicated,[ 9 , 17 , 22 , 25 ] even when the angle of the operative visual axis is approximately horizon, we could also maintain ergonomically comfortable posture and perform stably surgical manipulation.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…[ 11 ] However, when using ORBEYE for the midline suboccipital approach, the operator can perform stable manipulations in a comfortable posture from the rostral end of the patient with slight head-down position, regardless of the operative site and visual axis. In addition, as we previously indicated,[ 9 , 17 , 22 , 25 ] even when the angle of the operative visual axis is approximately horizon, we could also maintain ergonomically comfortable posture and perform stably surgical manipulation.…”
Section: Discussionmentioning
confidence: 79%
“…[ 9 , 17 , 21 , 22 ] In our previous reports, we have noted that stable and comfortable microsurgery can be performed with ORBEYE regardless of the operative visual axis, because it is not necessary for the operator to sit along the visual axis of the exoscope. [ 9 , 17 , 22 , 25 ] In particular, ORBEYE facilitates ergonomic microsurgery when the angle of the operative visual axis is set to overhang. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…15,16) Then, we have previously reported that the ORBEYE is ergonomically superior to a microscope. [17][18][19][20][21][22] In the present case, using ORBEYE, we set the angle of the operative visual axis approximately horizontally and manipulated it for a comfortable posture during the mucosal repair. Thus, while performing the mucosal repair using conventional microscopy is possible, we believe ORBEYE may offer a highly convenient and efficient approach.…”
Section: Discussionmentioning
confidence: 99%